Nano- and Microcomposites for Electrical Engineering Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In a dedicated Special Issue, the journal Polymers has compiled papers on the current trends and research directions within the preparation, characterization and application of polymer-based composite materials in electrical engineering applications. In recent times, this type of material has evolved to become one of the most thoroughly investigated materials, stimulated by the demand for the resource-efficient assembly of generators, transformers, communication devices, etc. Novel composites are to be used as insulating materials with high thermal conductivity and excellent temperature stability, through which premature ageing and degradation of devices shall be avoided or at least reduced. This Special Issue comprises twelve contributions by internationally renowned researchers; to mention Petru V. Nothinger (University Politehnica of Bucharest), Alun S. Vaughan (University of Southampton), Stanislaw M. Gubanski (Chalmers University of Technology), Michael Muhr (Graz University of Technology), Johan J. Smit (TU Delft), and Ulf W. Gedde (KTH Royal Institute of Technology) as prominent examples. The state-of-the-art research and technology of the area ‘micro- and nanocomposites for electrical engineering applications’ has been summarized in three review articles, while the current research trends and the development and characterization of novel materials have been described in eight original research articles. Stimulated by the vivid current interest in this topic, this Special Issue of Polymers has additionally been compiled in a book version.